SELF-DIRECTED CAREERS IN THE NEW WORLD OF WORK: PROTEAN CAREER ORIENTATION AND CAREER SELF-EFFICACY AS FOUNDATIONS FOR CAREER SUSTAINABILITY: A NARRATIVE REVIEW - I Kadek Andika Budi Utama; Nuh Luh Sri Kasih (STMIK Indonesia Banda Aceh, 2026)
Changes in the world of work driven by digitalization, hybrid work, the gig economy, and organizational restructuring have made careers increasingly non-linear and require individuals to take a more active role in managing their career trajectories. This narrative review synthesizes international literature from reputable journals to explain how Protean Career Orientation (PCO)-a self-directed and values-driven career orientation-contributes to career sustainability through enhanced career self-efficacy. Drawing on sustainable career models that emphasize health, happiness, and productivity, as well as the social cognitive career theory framework, the article proposes that Protean Career Orientation strengthens individuals' confidence in making career decisions, acquiring new skills, and navigating change. Career self-efficacy, in turn, promotes adaptive behaviors such as career self-management, lifelong learning or upskilling, networking and personal branding, and job crafting, which ultimately enhance employability, subjective career success, and well-being as indicators of career sustainability. This review also highlights the importance of context (career shocks, work flexibility) and organizational support (learning culture, coaching, access to training) as triggers and amplifiers of these processes. Finally, the article presents a conceptual model and narrative propositions that can serve as a basis for empirical research and as practical guidance for human resource development in the new world of work.